2014
DOI: 10.1192/bjp.bp.112.116285
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive–behavioural therapy for the symptoms of schizophrenia: systematic review and meta-analysis with examination of potential bias

Abstract: Cognitive-behavioural therapy has a therapeutic effect on schizophrenic symptoms in the 'small' range. This reduces further when sources of bias, particularly masking, are controlled for.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
310
2
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(352 citation statements)
references
References 101 publications
(187 reference statements)
14
310
2
13
Order By: Relevance
“…Knowledge of group assignment in clinical trials can affect participant responses and induce researcher bias, potentially giving a skewed representation of treatment efficacy (Schulz, Chalmers, & Altman, 2002). For example, a recent metaanalysis by Jauhar et al (2014) reported that the effect of cognitive behavioral therapy on the symptoms of psychosis was lower when assessments were made by interviewers blind to treatment allocation. By ensuring high quality investigation of the efficacy of self-help for psychosis, inflated effect sizes may be avoided, thereby providing a clearer view of the effect of self-help interventions on outcomes.…”
Section: P R E P U B L I C a T I O N C O P Ymentioning
confidence: 99%
“…Knowledge of group assignment in clinical trials can affect participant responses and induce researcher bias, potentially giving a skewed representation of treatment efficacy (Schulz, Chalmers, & Altman, 2002). For example, a recent metaanalysis by Jauhar et al (2014) reported that the effect of cognitive behavioral therapy on the symptoms of psychosis was lower when assessments were made by interviewers blind to treatment allocation. By ensuring high quality investigation of the efficacy of self-help for psychosis, inflated effect sizes may be avoided, thereby providing a clearer view of the effect of self-help interventions on outcomes.…”
Section: P R E P U B L I C a T I O N C O P Ymentioning
confidence: 99%
“…(2) In general, one of the recurring controversies around meta-analyses is that studies are excluded based on the (sometimes idiosyncratic) criteria of authors, which can result in very different findings between meta-analyses on the same topic (Murray, 2014). As an illustration of this, a recent metaanalysis on CBTp by the same group (Van der Gaag et al 2014) arrived at very favorable conclusions -much in contrast to some other metaanalyses on CBTp that came out around the same time (Lynch et al 2010;Jauhar et al 2014;Mehl et al 2015). The authors of the latest one (Mehl et al 2015) indicate that the meta-analysis by van patients with high baseline paranoia scores generally benefit most from metacognitive intervention and contrast the effect size of the three studies with the highest baseline delusions scores, including the one by So et al (2015), against studies with the lowest delusions scores.…”
mentioning
confidence: 74%
“…Nevertheless, even critics of CBT agree that there is a real, albeit small effect size advantage for CBT over and above medication alone (8). Notably, the investigators found no evidence of publication bias in these studies (8).…”
Section: Schizophrenia and Related Psychotic Disordersmentioning
confidence: 99%